2014
DOI: 10.1007/s13197-014-1369-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture on the physical properties of three varieties of kenaf seeds

Abstract: The physical properties of three kenaf varieties were evaluated as a function of moisture contents varying from 7.67 to 26.21, 7.35 to 25.96 and 7.27 to 25.53 % (dry basis) for cv. Everglades, Tainung and SF-459, respectively. The results showed that the increase in the moisture content of the kenaf seeds linearly decreased the bulk density, true density and rupture force, whereas it linearly increased the length, width, thickness, arithmetic mean diameter, geometric mean diameter, sphericity, surface area, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 26 publications
9
14
1
Order By: Relevance
“…It is shown in Table 6 that the linear model, adjusted itself properly to the data of the experimental terminal speed, with a good determination coefficient (R²), and low relative average error (P), below 10%, the same tendency was found by other authors working with other grains, such as the ones observed by Ahmadi and Siahsar (2011) and Izli (2015).…”
Section: Aerdynamic Property Equation R² P (%) Terminal Speedsupporting
confidence: 73%
See 1 more Smart Citation
“…It is shown in Table 6 that the linear model, adjusted itself properly to the data of the experimental terminal speed, with a good determination coefficient (R²), and low relative average error (P), below 10%, the same tendency was found by other authors working with other grains, such as the ones observed by Ahmadi and Siahsar (2011) and Izli (2015).…”
Section: Aerdynamic Property Equation R² P (%) Terminal Speedsupporting
confidence: 73%
“…According to Table 1, a decrease of 8.49, 10.39 and 6.49% for axis length (a axis), width (b axis) and density (c axis) can be observed for beans grains, respectively, in relation to its initial dimensions, with water content reduction of 32.89 up to 13.62 (%d.b.). This way, it can be verified that beans grains presented disuniform variations in the various axes, as verified in other studies (Siqueira et al, 2012b;Oliveira et al, 2014;Ren et al, 2014;Izli, 2015). From the determination of these variants of the product with water content reduction, the work performed by drier devisors is optimized, and it is feasible for them to enhance the drying system, taking into account factors such as air flow direction, product movement into drier, among other parameters and related processes (Araujo et al, 2015).…”
Section: Physical Propertiessupporting
confidence: 63%
“…The results also showed negative correlation of the true density and bulk density with moisture content. Moisture content of the kenaf seeds was negatively associated with bulk density, true density and rupture force, while it linearly increased the length, width, thickness, arithmetic mean diameter, geometric mean diameter, sphericity, surface area, seed volume, thousand seed mass, porosity, angle of repose and terminal velocity (Izli, 2015). The static coefficient of friction, filling and emptying angle of repose of kenaf seed increased linearly against the various surfaces like stainless steel, aluminum and glass in the same moisture range.…”
Section: Physical and Mechanical Properties Of Kenaf And Roselle Seedmentioning
confidence: 94%
“…In order to correctly design technical means to process, transport, and store these materials, it is necessary to understand their physical properties [7][8][9]. One of the most relevant physical properties of these materials which impacts the course of these technical processes is the external friction of the materials [10][11][12][13][14]. External friction in these types of materials means the friction which occurs between the construction material and the granular material [4].…”
Section: Introductionmentioning
confidence: 99%
“…The main factor which has been studied up to this point has been the water content of the materials. The impact of moisture on the value of the force of friction in plant granular materials has been studied by numerous researchers [10][11][12][13][16][17][18][19][20]. All of these studies have indicated an increase in static and kinetic friction along with an increase in moisture for plant granular materials.…”
Section: Introductionmentioning
confidence: 99%